Phytochemical Properties of Berries Decoction Extract and Evaluation of its Protective Activity Against Acetic Acid-Induced Ulcerative Colitis in Rats - Houcem Sammari; Saber Jedidi; Houcine Selmi; Mourad Jridi; Ala Ayari; Hichem Sebai (SAGE Publishing, 2024)
The present study aims to evaluate the protective effect of Crataegus azarolus berries decoction extract (CAB-DE) against acetic acid-induced ulcerative colitis as well as the mechanisms implicated in such protection. Adult male Wistar rats were separated into seven groups: Control (H 2 O), acetic acid (AA), AA + various doses of CAB-DE (100, 200, and 400 mg/kg, b.w.,p.o. ), and AA + sulfasalazine (100 mg/kg, b.w.,p.o. ) or gallic acid (50 mg/kg, b.w.,p.o. ) during 10 days. All rats were kept fasting overnight and ulcerative colitis was induced by rectal infusion of AA (300 mg kg −1 , b.w. ) (3%, v/v, 5 mL kg −1 b.w ), for 30 s. The colon was rapidly excised and macroscopically examined to measure ulcerated surfaces and the ulcer index. In vitro, we found that CAB-DE exhibited a high antioxidant activity against DPPH radical (IC 50 = 164.17 ± 4.78 μg/mL). In vivo , pretreatment with CAB-DE significantly protected the colonic mucosa against AA-induced damage by stimulating mucus secretion, reducing ulcer index as well as histopathological changes. Also, CAB-DE limited the oxidative status induced by AA in the colonic mucosa, as assessed by MDA and H 2 O 2 increased levels and the depletion of both enzymatic activities and non-enzymatic levels. In addition, AA intoxication increased iron and calcium levels in colonic mucosa and plasma, while CAB-DE pretreatment regulated all intracellular mediators deregulation and significantly reduced inflammatory markers such as CRP (1.175 ± .04 ─ .734 ± .06 μg/dl) and ALP (161.53 ± 5.02 ─ 98.60 ± 4.21 UI/L) levels. We suggest that CAB-DE protected against AA-induced ulcerative colitis due in part to its antioxidant and anti-inflammatory properties.